Social capital in Mexico moderates the relationship of uncertainty and cooperation during the SARS‐COV‐2 pandemic - Cruz Torress, Christian Enrique; Martin Del Campo Rios, Jaime (2021)
This study proposes that, given the coronavirus disease 2019 pandemic, its sanitary restrictions, and the associated economic effects, citizens perceive higher uncertainty and tend to reduce their willingness to cooperate with others. Community social capital refers to a set of norms of re- ciprocity, trust, and civic engagement networks that pro- mote trust, reciprocal help, and cooperation for mutual benefits. It is also suggested that it can help alleviate ne- gative effects of the pandemic in communities, by reducing uncertainty and its harmful effects on cooperation. These hypotheses were tested in a sample of 565 inhabitants of Mexico, who answered an online survey with measure- ments of social capital, uncertainty, and willingness to co- operate in the face of the pandemic. The relationships between variables were analyzed in two structural equation models, which show adequate goodness of fit, where higher levels of uncertainty generated by the pandemic were associated with a greater disposition to non- cooperation with others, while social capital moderated this relation decreasing negative effects of uncertainty on noncooperation. The value of social capital is discussed as a resource worth preserving and promoting in communities to strengthen them, so that they are better able to face health or economic contingencies.